Management of post partum complete eversion of uterus in graded Murrah buffalo - Ingawale, Maheshkumar Vitthalrao; Siddqui, Moiz; Thorat, Milind Gonduji; Waghmare, Sunil Pandurang; Pawshe, Chaityna Hemant (Buffalo Bulletin, 2020)
An unusual case of complete eversion of uterus along with cervix and vagina following a normal parturition in graded Murrah buffalo and its successful management is reported in the present article.